The Influence of Work Ethics and Morality on Organizational Performance through Organizational Commitment as a Mediating Variable (Empirical Study at PT XYZ Tbk) - Ali, Mariyuana Abdussamad; Prilaksono, Kursusantyo Dudung; Dayona, Gurawan; Sofiati, Nunung Ayu (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
Organizational performance today increasingly relies on the quality of human resources, not only in terms of technical competence but also in ethical integrity and moral orientation. Amid growing concerns over the decline of employee accountability and loyalty in large corporations such as PT XYZ Tbk, there is a critical need to examine the contribution of personal values—particularly work ethics and morality—in driving organizational performance. Previous Studies. Although several prior studies have demonstrated that work ethics and morality play a significant role in shaping organizational commitment (Yousef, 2001; Salahudin et al., 2016; Rokhman, 2010), the integrative relationship among these three variables, particularly with commitment as a mediating factor, remains underexplored in the context of Indonesian corporations. Novelty/Originality. This study proposes an empirical model to examine the influence of work ethics and morality on organizational performance through the mediation of organizational commitment. Using the Structural Equation Modeling (SEM) approach, the study investigates both direct and indirect relationships among these variables and establishes a strong theoretical framework for understanding how individual ethical values contribute to collective organizational outcomes. Research Problem. Does work ethics and morality influence organizational performance directly or indirectly through organizational commitment as a mediating variable? Research Objective. This study aims to examine the direct and indirect effects of work ethics, morality, and organizational commitment on organizational performance and to provide conceptual and practical insights into these relationships in the context of a publicly listed Indonesian company. Practical Implications. The findings of this study can be utilized by human resource managers to design ethical workplace interventions, strengthen employees’ emotional attachment to the organization, and enhance sustainable performance. Value Added. By integrating ethical dimensions into organizational behavior analysis, this study enriches the academic literature and highlights the importance of aligning personal morality with institutional performance goals, particularly in the face of transformation pressures and increasingly complex stakeholder expectations.